Open access follow up for inflammatory bowel disease: pragmatic randomised trial and cost effectiveness study. Issue 7234 (26th February 2000) - William, J G; Cheung, W Y; Russell, I T; Cohen, D R; Longo, M; Lervy, B
Abstract: Objective: To evaluate whether follow up of patients with inflammatory bowel disease is better through open access than by routine booked appointments. Design: Pragmatic randomised controlled trial. Setting: Two district general hospitals in Swansea and Neath, Wales. Participants: 180 adults (78 with Crohn's disease, 77 ulcerative or indeterminate colitis, 25 ulcerative or idiopathic proctitis) recruited from outpatient clinics during October 1995 to November 1996. Intervention: Open access follow up according to patient need. Main outcome measures: Generic (SF-36) and disease specific (UK inflammatory bowel disease questionnaire UKIBDQ) quality of life, number of primary and secondary care contacts, total resource use, and views of patients and general practitioners. Results: There were no differences in generic or disease specific quality of life. Open access patients had fewer day visits (0.21 v 0.42, P<0.05) and fewer outpatient visits (4.12 v 4.64, P<0.01), but some patients had difficulty obtaining an urgent appointment. There were no significant differences in specific investigations undertaken, inpatient days, general practitioner surgery or home visits, drugs prescribed, or total patient borne costs. Mean total cost in secondary care was lower for open access patients (P<0.05), but when primary care and patient borne costs were added there were no significant differences in total costs to the NHS or to society. General practitioners and patients preferred open access. Conclusions: Open access follow up delivers the same quality of care as routine outpatient care and is preferred by patients and general practitioners. It uses fewer resources in secondary care but total resource use is similar. Better methods of ensuring urgent access to outpatient clinics are needed.